2019
DOI: 10.1093/cid/ciz1145
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Infection Screening Among Gay, Bisexual, and Other Men Who Have Sex With Men Prescribed Pre-exposure Prophylaxis in Baltimore City, Maryland

Abstract: Background Human immunodeficiency virus pre-exposure prophylaxis (PrEP) clinical guidelines recommend men who have sex with men (MSM) PrEP users be screened biannually for syphilis and gonorrhea/chlamydia at all anatomic sites. We sought to determine the proportion screened and positive by STI and anatomic site at PrEP initiation and PrEP-care visits and patient-level characteristics associated with screening among MSM PrEP users in Baltimore City, Maryland. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 25 publications
3
16
1
Order By: Relevance
“…Several factors have been found to be associated with more recent or comprehensive STI screening: younger age, white race, college education, reporting exposure at anatomical sites that may trigger screening, and previous syphilis diagnoses [7,13,15,16]. We additionally found that residence in the Southeast was associated with inconsistent urogenital and rectal STI screening, after adjusting for potential confounders.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Several factors have been found to be associated with more recent or comprehensive STI screening: younger age, white race, college education, reporting exposure at anatomical sites that may trigger screening, and previous syphilis diagnoses [7,13,15,16]. We additionally found that residence in the Southeast was associated with inconsistent urogenital and rectal STI screening, after adjusting for potential confounders.…”
Section: Discussionmentioning
confidence: 70%
“…This study contributes to the growing literature on patterns of STI screening within PrEP care. With the exception of one national study [14], research has been limited to individual clinics or health systems, often with limited sample sizes [7,13,15,16]. These studies analyze a variety of data streams, including electronic health records, health insurance claims, or laboratory screening [15,16,27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations